Screening of erm Gene of Inducible Clindamycin Resistant Staphylococcus aureus - Timsina, Roshan; Timalsina, Bivek; Singh, Anjana (Journal of Institute of Science and Technology, 2019)
Antibiotic resistance exhibited by Staphylococcus aureus is a growing global concern. This work was undertaken to determine the prevalence rate of inducible clindamycin resistant S. aureus in nasal sample and detect ermB gene in the isolates with inducible clindamycin resistance. Nasal swabs were collected from the school children and cultured on Mannitol Salt Agar (MSA) and Blood Agar (BA) for observation of colony morphology. Gram staining and biochemical test (catalase, oxidase, O-F and coagulase) were performed for further identification of the bacteria. The Kirby-Bauer disc diffusion method using a cefoxitin disc (30 μg) was used to detect methicillin resistant S. aureus (MRSA). All, the MRSA isolates were tested for ermB gene by PCR amplification. Among 64 S. aureus isolates, 17 (26 %) were MRSA. The prevalence of Inducible clindamycin resistant S. aureus (iMLSB) isolates was 23.4 % in the S. aureus isolates. All the isolates of MRSA were resistant to penicillin, while 88.2 % were sensitive to gentamicin. The prevalence of ermB gene was 3.1 % in the total S. aureus isolates and 11.7 % MRSA showed the presence of this gene. Routinely performing a D-test in laboratory will guide the clinicians on the rationale use of clindamycin and improving hygienic practices can reduce the spread of inducible clindamycin resistance.